2003
DOI: 10.4049/jimmunol.171.3.1304
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Dibasic Amino Acid Motif Within the C Terminus of the P2X7 Nucleotide Receptor Results in Trafficking Defects and Impaired Function

Abstract: Activation of the P2X7 receptor by extracellular nucleotides modulates multiple immune functions, including inflammatory mediator production, membrane fusion events, and apoptosis. Previous studies have revealed that the C terminus of this multimeric cation channel possesses a lipid-interaction motif that has been proposed to regulate receptor function. This domain is homologous to the LPS binding region of the LPS binding protein, and we demonstrated that two basic residues (Arg578, Lys579) within this motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 43 publications
3
67
0
Order By: Relevance
“…The conserved YXXXK motif found in Cterminal of P2XRs other than P2X7R is necessary for their expression at the cell surface [24]. In human P2X7R, a motif located in the distal region of its C-terminus tail is necessary for proper receptor trafficking; progressive deletions of this tail between residues 551 and 581 are nonfunctional and are not found in the plasma membrane [10,41]. The same motif is also involved in pore dilation [45,48].…”
Section: Discussionmentioning
confidence: 99%
“…The conserved YXXXK motif found in Cterminal of P2XRs other than P2X7R is necessary for their expression at the cell surface [24]. In human P2X7R, a motif located in the distal region of its C-terminus tail is necessary for proper receptor trafficking; progressive deletions of this tail between residues 551 and 581 are nonfunctional and are not found in the plasma membrane [10,41]. The same motif is also involved in pore dilation [45,48].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the region also alter the permeability of P2X receptor channels for divalent ions [86]. The second membrane-spanning domain is also involved in protein folding and assembly of P2X subunits [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…However, P2X 7 Rs have a long intracellular C-terminal end, being 120 -200 amino acids longer compared with other P2X receptors (3,17). This long C-terminal end has been proposed to be responsible for most of the specific biophysical properties of the P2X 7 R with numerous functions such as connecting the receptor to structures responsible for the large pore formation (3,17), recently proposed as being pannexin-1 (18), the interaction with adaptor and signaling proteins (19,20), the regulation of P2X 7 R trafficking to the plasma membrane (21,22), and the modulation of channel gating (23). Recently, we demonstrated that rat P2X 7 R C terminus is also displaying a novel 1-5-16 calmodulin-binding motif responsible for a calcium-dependent facilitation (24).…”
mentioning
confidence: 99%